Development of control system for inverted pendulum using PID and fuzzy logic - Cheang Peck Yee (2023)
This thesis reports the development of control system for an inverted pendulum on a cart system using PID and fuzzy logic. The basic aim is to balance the inverted pendulum in upright position. The work starts with the modeling of inverted pendulum on a cart and development of fuzzy rule based controller and PID based controller for controlling of real inverted pendulum. The programmed used for this project is Microsoft Visual Basic 6.0 and Matlab. The system consists of motor driver, AC servo motor, lead screw and the inverted pendulum mount on a cart.